(untitled) (Linguostylistic Studies, 2020)
The article analyzes the features of the figurative means functioning in online advertising (primarily metaphors and metonyms). It has been proved that in the structure of the advertisement on the Internet, commonly-used or trite metaphorical models (the world of smth, a key to understanding of smth, a family of smth, the style of smth, the art of smth, and others) predominate. The level of imagery of a language means in this case significantly depends on the context and creative approach of the author. Original imaginary figurative means in online advertising appear much less often, which is due to the increased complexity of their interpretation and the complicated structure of connotations. In online advertising, the distinctive personification metaphors and various metonyms dominate. They form positive connotations, enhance the emotionality and expressiveness of advertising, as well as save language resources by deepening the semantics and imagery of the text. Quite often metaphorical epithets appear in advertising texts, although in general the specifics of advertising are determined by ugly definitions. Comparisons and hyperboles are elements rarely used in advertising. In general, every second message in online advertising contains figurative language means.